The The Effect Of Service Quality And Student Satisfaction On Student Loyalty - Lika Trisela; Hermanto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
Student loyalty is the most impotant part of measuring the reputation of a school. This study aims to determine: (1) the effect of service quality on student satisfaction, (2) the effect of student satisfaction on student loyalty, and (3) the effect of service quality on student loyalty. This study uses a survey quantitative approach. It is conducted at Private High School in Kutoarjo District. The sample of this research is 146 students. Data collection techniques using is questionnaires. While data analysis using SmartPLS. The results of this study show that: (1) Service quality has positive and significant effect on student satisfaction, (2) Student satisfaction has positive and significant effect on student loyalty, and (3) Service quality has positive and significant effect on student loyalty.